2017
DOI: 10.1001/jamadermatol.2016.6136
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Contact Dermatitis Registry Data on Contact Allergy in Children With Atopic Dermatitis

Abstract: IMPORTANCE Atopic dermatitis (AD) and allergic contact dermatitis (ACD) have a dynamic relationship not yet fully understood. Investigation has been limited thus far by a paucity of data on the overlap of these disorders in pediatric patients.OBJECTIVE To use data from the Pediatric Contact Dermatitis Registry to elucidate the associations and sensitizations among patients with concomitant AD and ACD. DESIGN, SETTING, AND PARTICIPANTSThis retrospective case review examined 1142 patch test cases of children you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 33 publications
4
62
1
Order By: Relevance
“…As the presence of these surfactants is frequent in daily cosmetic products (shampoo, liquid soap, toothpaste), sensitization to the agents could easily occur. High prevalences of CAPB/DMAPA contact allergies have been found by other authors as well, but are underreported as they are often not tested, as they are not in the EBS and only tested on indication 25, 48, 49. The allergenic potential of CAPB has been disputed, and it is argued whether CAPD is a true allergen or only an irritant 50.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the presence of these surfactants is frequent in daily cosmetic products (shampoo, liquid soap, toothpaste), sensitization to the agents could easily occur. High prevalences of CAPB/DMAPA contact allergies have been found by other authors as well, but are underreported as they are often not tested, as they are not in the EBS and only tested on indication 25, 48, 49. The allergenic potential of CAPB has been disputed, and it is argued whether CAPD is a true allergen or only an irritant 50.…”
Section: Discussionmentioning
confidence: 96%
“…High prevalences of CAPB/DMAPA contact allergies have been found by other authors as well, but are underreported as they are often not tested, as they are not in the EBS and only tested on indication. 25,48,49 The allergenic potential of CAPB has been disputed, and it is argued whether CAPD is a true allergen or only an irritant. 50 As CAPB and DMAPA only show crescendo and plateau patterns in our dynamic pattern analysis, we think that at least in this population they reflected true allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of allergic contact dermatitis (ACD) is higher in children than previously recognized . Consort dermatitis refers to an allergic contact dermatitis caused by transfer from an intimate contact to a sensitized patient .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it has also been suggested that the impaired skin barrier function in AD could increase the risk of sensitization to contact allergens. Frequent skin exposure to chemical substances in topical treatments, for example moisturizers and topical medicaments, at an early age and for long periods may also contribute to a heightened risk for skin sensitization among individuals with AD . Moisturizers often contain contact allergens such as preservatives and fragrances .…”
mentioning
confidence: 99%
“…Frequent skin exposure to chemical substances in topical treatments, for example moisturizers and topical medicaments, at an early age and for long periods may also contribute to a heightened risk for skin sensitization among individuals with AD . Moisturizers often contain contact allergens such as preservatives and fragrances . This is true also for products labelled as hypoallergenic .…”
mentioning
confidence: 99%